UPAYA MENGHAMBAT KEMATIAN BIROKRASI (Aplikasi Learning Organization dalam Organisasi Pemerintahan) - Saeful Millah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
It is no doubt that bureaucracy has an important role in the provision of publicservices. However, for many reasons, the performance of our bureaucracy is still far from what people expect. Its resistance to change, in addition to other unacceptable manners, is a critical factor that makes the bureaucracy unable to perform as expected. The rise of Learning Organization through which a concept of powerful organization formation is offered, is expectedly able to become the leverage for or bureaucracy to overcome its impediments. In essence, learning organization recommends that, in order to be successful like private firms or companies, the bureaucracy needs to accelerate its learning process and adjust itself to the rapid, global change. The importance of learning organization derives from the idea that ‘the survival of the fittest’ is quickly amending to ‘the survival of the fittest to learn’. Despite the good concept, the idea of learning organization is not easy to put into practice within the bureaucratic system due to its unacceptable ‘cultures’, attitudes and paradigm that are not in line with the spirit of learning organization. Therefore, what we need to do in the first place is to change the bureaucracy in terms of its structure and its intrinsic foundations by which it operates: values, norms, and paradigm. Another key aspect is to change the way people manage the bureaucracy.